My tax organizer mobile app: Simplifying tax documents organization / Norhayati Sulaiman ... [et al.] - Sulaiman, Norhayati; Khair Anwar, Irda Syahira; Sayed Rohani, Syed Redzwan; Ghuslan, Mohamad Iruwan (2024)
Managing tax-related financial documents is challenging for individuals and businesses, especially small enterprises. Difficulties in organizing paper-based documents and manual tracking result in inefficiencies, stress, and compliance issues. Taxpayers often misplace important documents and struggle to recall details of their deductible expenses. Additionally, a lack of understanding regarding available tax deductions causes many taxpayers to underutilize tax reliefs, thereby paying more tax than necessary. The transition to tax e-filing further complicates document management, as taxpayers face challenges in tracking scattered digital documents. To address these issues, the researcher developed "MyTax Organizer," a mobile app simplifying tax document management. Users can capture, organize, and store receipts, invoices, bills, and more on their devices. It offers a centralized, user-friendly solution, enhancing convenience and efficiency in tax preparation.